Demographic Trends of Adults in New York City Opioid Treatment Programs—An Aging Population. (10th November 2015) - Han, Benjamin; Polydorou, Soteri; Ferris, Rosie; Blaum, Caroline S.; Ross, Stephen; McNeely, Jennifer
Abstract : Background : The population of adults accessing opioid treatment is growing older, but exact estimates vary widely, and little is known about the characteristics of the aging treatment population. Further, there has been little research regarding the epidemiology, healt h status, and functional impairments in this population. Objectives : To determine the utilization of opioid treatment services by older adults in New York City. Methods : This study used administrative data from New York State licensed drug treatment programs to examine overall age trends and characteristics of older adults in opioid treatment programs in New York City from 1996 to 2012. Results : We found significant increases in utilization of opioid treatment programs by older adults in New York City. By 2012, those aged 50–59 made up the largest age group in opioid treatment programs. Among older adults there were notable shifts in demographic background including gender and ethnicity, and an increase in self-reported impairments. Conclusions/Importance : More research is needed to fully understand the specific characteristics and needs of older adults with opioid dependence.